Knowledge, attitudes and practices regarding sexually transmitted infections in human medicine interns at a public university in 2023 - Arenas Garcia, Eduardo (2025)
Introduction: Sexually transmitted infections (STIs) represent a significant global health issue. In Peru, their high prevalence and deficiencies in epidemiological surveillance highlight the need for solid training for future healthcare professionals. Objective: To determine the relationship between knowledge, attitudes, and practices regarding STIs among medical interns. Methods: A quantitative, observational, descriptive-correlational, and cross-sectional study was conducted. Ninety-three medical interns from a public university participated. A structured questionnaire was used to assess knowledge, attitudes, and practices regarding STIs. Data were analyzed using IBM SPSS v29 software with chisquare tests. Results: 34.4% of interns had deficient knowledge about STIs, 45.1% had regular knowledge, and 20.4% had adequate knowledge. Regarding attitudes, 96.7% adopted a positive attitude, and 94.6% exhibited positive practices. No significant relationship was found between knowledge, attitudes, and practices (p>0.05). Conclusion: Despite positive attitudes and practices, knowledge about STIs is insufficient among interns, highlighting the need to improve their training in this area.